Electrode active material layer for all-solid secondary battery, and all-solid secondary battery using the same
Patent Information
- Application Number
- JP2023141523
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0009】 本発明によれば、全固体二次電池の内部低意向を低減させることができる。
Smart Images

Figure 2025034862000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode active material layer for an all-solid-state secondary battery and an all-solid-state secondary battery using the same. [Background technology]
[0002] In recent years, research and development of all-solid-state batteries using oxide-based or sulfide-based solid electrolytes has been actively conducted. Solid electrolytes are materials mainly composed of ion conductors that can conduct ions in a solid state. Therefore, all-solid-state batteries have the advantage that, in principle, various problems caused by flammable organic electrolytes do not occur, as in conventional liquid-based batteries using non-aqueous electrolytes.
[0003] As one type of solid electrolyte, sulfide solid electrolytes containing elemental sulfur are known to exhibit excellent ion conductivity. On the other hand, there is a problem that if the content of organic solvent remaining in the sulfide solid electrolyte is large, the amount of hydrogen sulfide generated over time also increases. Here, Patent Document 1 discloses that if the content of organic solvent in the sulfide solid electrolyte is 0.95 mass% or less, such generation of hydrogen sulfide over time can be prevented. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 203224 Summary of the Invention [Problem to be solved by the invention]
[0005] However, according to the investigations of the present inventors, it was found that when the content of the organic solvent in the sulfide solid electrolyte is 0.95 mass % or less, the internal resistance of an all-solid-state secondary battery produced using the electrolyte may increase in some cases.
[0006] Therefore, an object of the present invention is to provide a means capable of reducing the internal resistance of an all-solid-state secondary battery. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have found that the above problems can be solved by adding, to an electrode active material layer of an all-solid-state secondary battery, in addition to a sulfide solid electrolyte, an organic solvent having a relative dielectric constant of 4.5 or less at 20° C. in an amount of 1.0 to 9.0 mass % relative to 100 mass % of the sulfide solid electrolyte, and have thus completed the present invention.
[0008] That is, one embodiment of the present invention is an electrode active material layer for an all-solid-state secondary battery, comprising an electrode active material, a sulfide solid electrolyte, and an organic solvent having a relative dielectric constant of 4.5 or less at 20°C, wherein the content of the organic solvent is 1.0 to 9.0 mass% relative to 100 mass% of the sulfide solid electrolyte. Effect of the Invention
[0009] According to the present invention, it is possible to reduce internal low pressure in an all-solid-state secondary battery. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic overall structure of a stacked-type (internal parallel connection type) all-solid-state lithium secondary battery (stacked-type secondary battery) according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One embodiment of the present invention is an electrode active material layer for an all-solid-state secondary battery, comprising an electrode active material, a sulfide solid electrolyte, and an organic solvent having a relative dielectric constant of 4.5 or less at 20°C, wherein the content of the organic solvent is 1.0 to 9.0 mass% relative to 100 mass% of the sulfide solid electrolyte.
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the attached drawings. In the description of the drawings, the same elements are given the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are exaggerated for the convenience of explanation, and may differ from the actual ratios.
[0013] FIG. 1 is a cross-sectional view showing a schematic overall structure of a stacked type (internal parallel connection type) all-solid-state lithium secondary battery (hereinafter, also simply referred to as a "stacked type secondary battery") according to one embodiment of the present invention. The stacked type secondary battery 10a shown in FIG. 1 has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29 that is a battery exterior body. Here, the power generating element 21 has a structure in which a negative electrode, a solid electrolyte layer 17, and a positive electrode are stacked. The negative electrode has a structure in which a negative electrode current collector 11' and a negative electrode active material layer 13 containing a negative electrode active material are stacked. Then, a negative electrode intermediate layer 14 is disposed so as to be adjacent to the surface of the negative electrode active material layer 13 facing the solid electrolyte layer 17. The positive electrode has a structure in which a positive electrode active material layer 15 containing a positive electrode active material is disposed on the surface of a positive electrode current collector 11". The negative electrode, negative electrode intermediate layer, solid electrolyte layer, and positive electrode are laminated in this order, with the negative electrode intermediate layer 14 and the positive electrode active material layer 15 facing each other via the solid electrolyte layer 17. As a result, adjacent negative electrodes, negative electrode intermediate layers, solid electrolyte layers, and positive electrodes constitute one unit cell layer 19. Therefore, the stacked type secondary battery 10a shown in FIG. 1 can be said to have a structure in which a plurality of unit cell layers 19 are laminated and electrically connected in parallel. A negative electrode current collector 25 and a positive electrode current collector 27 that are conductive with the respective electrodes (negative electrode and positive electrode) are attached to the negative electrode current collector 11' and the positive electrode current collector 11", respectively, and have a structure in which they are sandwiched between the ends of the laminate film 29 and led out to the outside of the laminate film 29. A pressure member (not shown) applies a restraining pressure to the stacked secondary battery 10a in the stacking direction of the power generating element 21. Therefore, the volume of the power generating element 21 is kept constant.
[0014] As described above, one aspect of the present invention is an electrode active material layer for an all-solid-state secondary battery, the electrode active material layer including an electrode active material, a sulfide solid electrolyte, and a predetermined amount of a predetermined organic solvent. In the all-solid-state secondary battery, the electrode active material layer may be a positive electrode active material layer, a negative electrode active material layer, or both.
[0015] Hereinafter, main components of the all-solid-state battery according to the above-described embodiment will be described.
[0016] [Current collector] The current collectors (negative electrode current collector, positive electrode current collector) have a function of mediating the movement of electrons from the electrode active material layers (negative electrode active material layer, positive electrode active material layer). There is no particular limitation on the material constituting the current collectors. For example, metals such as aluminum, nickel, iron, stainless steel, titanium, and copper, and conductive resins can be used as the material constituting the current collectors. There is also no particular limitation on the thickness of the current collectors, but an example is 10 to 100 μm.
[0017] [Electrode active material layer] The electrode active material layer (positive electrode active material layer / negative electrode active material layer) contains an electrode active material (positive electrode active material / negative electrode active material) and a sulfide solid electrolyte. In this specification, unless otherwise specified, matters common to positive and negative electrodes will be referred to as "electrode".
[0018] (electrode active material) When the electrode active material layer for an all-solid-state battery according to the present embodiment is a positive electrode active material layer, the positive electrode active material layer contains a positive electrode active material capable of absorbing and releasing lithium ions. The positive electrode active material is not particularly limited as long as it is a material capable of releasing lithium ions during the charging process of the secondary battery and absorbing lithium ions during the discharging process. From the viewpoint of high capacity, it is preferable that the positive electrode active material contains a lithium transition metal composite oxide. The lithium transition metal composite oxide is a compound belonging to the space group R3m, and has a layered structure (layered rock salt structure) in which lithium atomic layers and transition metal atomic layers are alternately stacked. Therefore, by using such a positive electrode active material, the battery capacity of the all-solid-state secondary battery can be improved.
[0019] Examples of lithium transition metal composite oxides include LiCoO2, LiNiO2, LiMnO2, Li(Ni-Mn-Co)O2, Li(Ni-Co-Al)O2, and oxides in which some of these transition metals have been replaced with other elements. More preferably, composite oxides containing lithium and nickel are used, and even more preferably, Li(Ni-Mn-Co)O2 and oxides in which some of these transition metals have been replaced with other elements (hereinafter, also simply referred to as "NMC composite oxides") or Li(Ni-Co-Al)O2 and oxides in which some of these transition metals have been replaced with other elements (hereinafter, also simply referred to as "NCA composite oxides") are used, and particularly preferably, NMC composite oxides are used.
[0020] As described above, the NMC composite oxide and the NCA composite oxide also include composite oxides in which a part of the transition metal element is replaced by another metal element. In this case, the other elements include Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, V, Cu, Ag, Zn, etc., and are preferably Al, Sn, Nb, Ti, Zr, Mg, W, P, V, Ca, Sr, Cr, more preferably Al, Sn, Nb, Ti, Zr, Mg, P, Cr, and further preferably Al, Sn, Nb, Ti, Zr, Mg, from the viewpoint of improving cycle characteristics. However, the other metal elements that can replace the transition metal element of the NCA composite oxide are other than Al.
[0021] The lithium transition metal composite oxide as the positive electrode active material has a high theoretical discharge capacity, and is therefore preferably represented by the general formula (1): Li x Ni a M b N cO2 (wherein x, a, b, c, and d satisfy 0.8≦x≦1.1, a+b+c=1, 0.33≦a≦0.95, 0.05≦b≦0.67, and 0≦c≦0.10. M is one or more elements selected from the group consisting of Mn and Co, and N is one or more elements selected from the group consisting of Al, Sn, Nb, Ti, Zr, and Mg). Here, x represents the atomic ratio of Li, a represents the atomic ratio of Ni, b represents the atomic ratio of M, and c represents the atomic ratio of N. The composition of each element can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry.
[0022] From the viewpoint of realizing a higher discharge capacity, it is preferable that in the general formula (1), 0.80≦a≦0.95 (i.e., high-nickel composite oxide). In addition, when the electrode active material layer for an all-solid-state secondary battery according to this embodiment is a positive electrode active material layer, the effect of adopting the configuration according to this embodiment is particularly remarkable when a high-nickel composite oxide is used as the positive electrode active material. Therefore, from this viewpoint as well, it is preferable that the positive electrode active material contains a high-nickel composite oxide.
[0023] The positive electrode active material may contain an active material other than the above-mentioned lithium transition metal composite oxide. In some cases, two or more positive electrode active materials may be used in combination. However, the content ratio of the lithium transition metal composite oxide in the total amount (100 mass%) of the positive electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, still more preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass%.
[0024] The shape of the positive electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the positive electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50The value of can be measured by a laser diffraction scattering method.
[0025] The surface of the particles of the positive electrode active material is preferably coated with an inorganic compound other than the positive electrode active material. By adopting such a configuration, it is possible to prevent an increase in the interface resistance at the interface between the positive electrode active material and the sulfide solid electrolyte, and thus it can further contribute to the reduction of the internal resistance of the all-solid-state secondary battery. There is no particular restriction on the specific type and coating amount of the inorganic compound, and conventionally known knowledge can be appropriately referred to. In particular, from the viewpoint of a high effect of reducing the internal resistance, it is preferable that the inorganic compound contains lithium, oxygen, and one or more selected from the group consisting of niobium, phosphorus, boron, silicon, germanium, titanium, and zirconium. There is no particular restriction on the method of coating the surface of the particles of the positive electrode active material with the inorganic compound, and if it is a dry method, a milling device such as a planetary ball mill device can be used as a conventionally known method for attaching (attaching) a large number of other particles to the surface of the particles. In addition, in some cases, a mechanofusion system by Hosokawa Micron Corporation may be used. Furthermore, if the coating layer is formed by a wet method, it is possible to refer to JP 2009-266728 A and known literature (Xiaowen Xhan et al., Electrochimica Acta 300 (2019) 36-44, Seitaro Ito et al., Journal of Power Sources 248 (2014) 943-950), etc.
[0026] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is, for example, preferably in the range of 30 to 99 mass %, more preferably in the range of 40 to 90 mass %, and even more preferably in the range of 45 to 80 mass %.
[0027] When the electrode active material layer for an all-solid-state battery according to the present embodiment is a negative electrode active material layer, the negative electrode active material layer contains a negative electrode active material capable of absorbing and releasing lithium ions. The type of the negative electrode active material is not particularly limited, but may be a carbon material, a metal oxide, or a metal active material. Examples of the carbon material include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the metal oxide include Nb2O5, Li4Ti5O 12 , SiO, etc. Examples of the metal active material include, for example, metal elements such as In, Al, Si, and Sn, and alloys such as TiSi, La3Ni2Sn7, etc. Also, a metal containing Li may be used as the negative electrode active material. Such a negative electrode active material is not particularly limited as long as it is an active material containing Li, and examples of the negative electrode active material include Li metal and Li-containing alloys. Examples of the Li-containing alloy include, for example, an alloy of Li and at least one of In, Al, Si, and Sn. The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, more preferably in the range of 50 to 90 mass %, and even more preferably in the range of 55 to 80 mass %.
[0028] (solid electrolyte) The electrode active material layer includes a sulfide solid electrolyte containing S element. The sulfide solid electrolyte has high ionic conductivity in bulk and can better follow the volumetric changes of the electrode active material accompanying charging and discharging, which can improve the rate characteristics of the all-solid-state battery. Furthermore, by making the electrode active material layer thicker, it becomes possible to improve the energy density of the all-solid-state battery. In this specification, the term "solid electrolyte" refers to a material mainly composed of an ion conductor capable of ion conduction in a solid, and in particular, refers to a material having a lithium ion conductivity of 1×10 at room temperature (25° C.). -5 S / cm or more, and this lithium ion conductivity is preferably 1×10 -4 The lithium ion conductivity is 1.0 S / cm or more. The lithium ion conductivity can be measured by an AC impedance method.
[0029] In terms of being further excellent due to the above-described performance, the sulfide solid electrolyte preferably contains Li element, M element and S element, and the M element is a sulfide solid electrolyte containing at least one element selected from the group consisting of P, Si, Ge, Sn, Ti, Zr, Nb, Al, Sb, Br, Cl and I, and more preferably a sulfide solid electrolyte containing S element, Li element and P element.
[0030] The sulfide solid electrolyte may have a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of the sulfide solid electrolyte having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Further, examples of the sulfide solid electrolyte having a Li4P2S7 skeleton include a Li-P-S-based solid electrolyte called LPS. Also, as the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. More specifically, for example, LPS (Li2S-P2S5), Li7P3S 11 , Li 3.2 P 0.96 S, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 , or Li6PS5X (where X is Cl, Br or I), etc. are mentioned. Note that the description of "Li2S-P2S5" means a sulfide solid electrolyte formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. Among them, from the viewpoint that the sulfide solid electrolyte has high ionic conductivity and low volume elastic modulus and can follow the volume change of the electrode active material accompanying charge and discharge, preferably LPS (Li2S-P2S5), Li6PS5X (where X is Cl, Br or I), Li7P3S 11 , Li 3.2 P 0.96 S and Li3PS4 are selected from the group consisting of.
[0031] In addition to the sulfide solid electrolyte, the electrode active material may further contain other solid electrolytes such as an oxide solid electrolyte or a resin solid electrolyte. However, the proportion of the sulfide solid electrolyte in the solid electrolyte contained in the electrode active material layer is preferably 50 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 98 mass% or more, and most preferably 100 mass%.
[0032] The shape of the solid electrolyte may be, for example, a particulate shape such as a true sphere or an oval sphere, a thin film, etc. When the solid electrolyte is particulate, its average particle size (D50) is not particularly limited, but is preferably 0.01 μm or more and 40 μm or less, more preferably 0.1 μm or more and 20 μm or less, and even more preferably 0.5 μm or more and 10 μm or less.
[0033] The content of the solid electrolyte in the electrode active material layer is not particularly limited, but is, for example, preferably in the range of 1 to 70 mass %, more preferably in the range of 10 to 60 mass %, and even more preferably in the range of 20 to 55 mass %.
[0034] (Binder) The electrode active material layer preferably further contains a binder. The type of binder is not particularly limited, and a material that is conventionally known as a binder for an electrode active material layer of a secondary battery can be appropriately adopted. Among them, the binder preferably contains a fibrous binder. In this specification, the term "fibrous binder" refers to a binder that is mainly composed of fibers having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less in an observation image when a cross section of an electrode active material layer is observed using a scanning electron microscope (SEM). Here, the aspect ratio is calculated by dividing the maximum Feret diameter of the binder by the minimum Feret diameter. The maximum Feret diameter is the maximum distance between two parallel straight lines when the contour of the binder is sandwiched between the two parallel straight lines, and the minimum Feret diameter is the minimum distance between the two parallel straight lines when the contour of the binder is sandwiched between the two parallel straight lines. A certain binder is "mainly composed" of the above fibers means that the area ratio of the above fiber portion to the total area of the binder in the SEM observation image is 50% or more. A fibrous binder may include a portion other than the fiber having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less (a portion having an aspect ratio of less than 10 or a portion having a minimum Feret diameter of more than 0.2 μm). However, the area ratio of the portion other than the fiber to the total area of the fibrous binder in the SEM observation image must be less than 50%, preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less (the lower limit is 0%). The fibrous binder includes not only those composed of only one fiber, but also those having a configuration in which two or more fibers are connected to each other. Specific shapes of binders having a configuration in which two or more fibers are connected to each other include branched chain, radial, and net-like shapes, and shapes that are combinations of these. Here, a method for determining the maximum Feret diameter and the minimum Feret diameter in a binder having a configuration in which two or more fibers are connected to each other will be described. FIG. 2 is a schematic diagram showing an example of a branched chain fibrous binder. 2 has a configuration in which fiber X, fiber Y, and fiber Z are connected to each other. Each dashed line represents a line connecting the centers (1 / 2 width) of the widths of the fibers, and points A, B, and C represent the ends of each dashed line.The ends of each broken line coincide with the ends of the fibers. Point D represents the intersection of the three broken lines. That is, it can be said that the binder 30 shown in FIG. 2 has a shape in which fiber X from point A to point D, fiber Y from point B to point D, and fiber Z from point C to point D are bonded at point D. The maximum Feret diameter of fiber X in the binder 30 shown in FIG. 2 is defined as the distance from point A to point D. Similarly, the maximum Feret diameter of fiber Y is the distance from point B to point D, and the maximum Feret diameter of fiber Z is the distance from point C to point D. In addition, the minimum Feret diameter of fiber X is the minimum distance between two parallel straight lines when the contour of the binder (fiber) between point A and point D is sandwiched between the two parallel straight lines. The same applies to the minimum Feret diameters of fiber Y and fiber Z. In the binder 30 shown in FIG. 2, the fiber Y and the fiber Z are fibers having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less, while the fiber X has an aspect ratio of less than 10. However, since the area of the fiber X portion in the total area of the binder 30 is less than 50%, the binder shown in FIG. 2 can be said to be a fibrous binder. The type of fibrous binder is not particularly limited as long as it has the above-mentioned shape in the electrode active material layer, but a binder that can be fibrillated by applying a shear force can be preferably used. As the type of such a binder that can be fibrillated, polytetrafluoroethylene (PTFE), carboxymethyl cellulose, polyvinyl alcohol, and polyethylene are preferable, and polytetrafluoroethylene (PTFE) is more preferable. Only one type of fibrous binder may be used alone, or two or more types may be used in combination. In this specification, the description of the compound name of the binder may include not only the compound indicated by the compound name, but also a form in which a part of the terminal or side chain is substituted (modified) by another substituent. In cases where a portion of the terminals or side chains are substituted (modified) with other substituents, the proportion of structural units whose terminals or side chains are substituted (modified) with other substituents in 100 mol % of all structural units is preferably 10 mol % or less, and more preferably 5 mol % or less.
[0035] In addition, when the electrode active material layer contains a binder, it may contain a binder other than the fibrous binder (non-fibrous binder). The type of non-fibrous binder is not particularly limited, but styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), ethyl cellulose, and acrylic resin are preferable, and polyvinylidene fluoride (PVDF) is more preferable. The non-fibrous binder may be used alone or in combination of two or more types. As described above, the binder may include a form in which the terminal or part of the side chain is substituted (modified) with another substituent. However, the mass ratio of the fibrous binder to the entire binder in the electrode active material layer is preferably 50 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 98 mass% or more, and most preferably 100 mass%.
[0036] In another preferred embodiment, the electrode active material layer contains a fluorine-containing polymer compound as a binder. Among the fluorine-containing polymer compounds, an example of a fibrous binder is polytetrafluoroethylene (PTFE), and an example of a non-fibrous binder is polyvinylidene fluoride (PVDF). Since the fluorine-containing polymer compounds are compatible with the sulfide solid electrolyte, when the electrode active material layer contains such a fluorine-containing polymer compound as a binder, the contact property and ionic conductivity at the interface between the electrode active material (preferably the positive electrode active material) and the sulfide solid electrolyte can be improved.
[0037] (Conductive assistant) The electrode active material layer preferably further contains a conductive assistant in addition to the electrode active material. In particular, when the electrode active material layer is a positive electrode active material layer, the effect of adding the conductive assistant is high. The electronic conductivity of the conductive assistant is preferably 1 S / m or more, and 1×10 2 More preferably, it is 1×10 S / m or more. 4 More preferably, it is 1×10 S / m or more. 5 The upper limit of the electronic conductivity of the conductive additive is not particularly limited, but is usually 1×107 S / m or less.
[0038] The type of conductive assistant is not particularly limited, and conventionally known materials can be appropriately adopted as a conductive assistant for the electrode active material layer of the all-solid-state secondary battery. Examples of the conductive assistant include fibrous conductive assistants such as fibrous carbon. In this specification, the term "fibrous conductive assistant" refers to a conductive assistant having an aspect ratio of 10 or more and a minimum Feret diameter of 0.2 μm or less in an image observed using a scanning electron microscope (SEM). The type of fibrous carbon is not particularly limited as long as it has the above-mentioned shape, and includes carbon fiber (specifically, vapor grown carbon fiber (VGCF), polyacrylonitrile carbon fiber, pitch carbon fiber, rayon carbon fiber, activated carbon fiber, etc.), graphene, and carbon nanotubes (single-walled carbon nanotubes and multi-walled carbon nanotubes). Among them, carbon fiber is preferable. The fibrous conductive assistant (preferably fibrous carbon) may be used alone or in combination of two or more types.
[0039] On the other hand, when the electrode active material layer contains a conductive assistant, the conductive assistant may be a conductive assistant other than a fibrous conductive assistant (non-fibrous conductive assistant). The type of non-fibrous conductive assistant is not particularly limited, but includes metals such as aluminum, stainless steel (SUS), silver, gold, copper, titanium, alloys or metal oxides containing these metals, and carbon such as carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), but is not limited thereto. In addition, a particulate ceramic material or a resin material coated with the above-mentioned metal material by plating or the like can also be used as a conductive assistant. Only one type of non-fibrous conductive assistant may be used alone, or two or more types may be used in combination.
[0040] (Organic solvent) The electrode active material layer for an all-solid-state secondary battery according to this embodiment is characterized in that, in addition to the above-mentioned electrode active material and sulfide solid electrolyte, it further contains an organic solvent having a relative dielectric constant of 4.5 or less at 20°C in an amount of 1.0 to 9.0 mass% relative to 100 mass% of the sulfide solid electrolyte.
[0041] The dielectric constant is an index that indicates the polarity of a compound, and is a dimensionless quantity calculated as the ratio of the dielectric constant of the compound to the dielectric constant of a vacuum. The smaller the dielectric constant, the less polar the compound is.
[0042] Examples of organic solvents having a relative dielectric constant of 4.5 or less at 20°C include pentane (1.8), hexane (1.9), heptane (1.9), isooctane (1.9), octane (1.9), cyclohexane (2.0), dichlorodifluoromethane (2.1), 1,4-dioxane (2.2), tetrachloromethane (2.2), tetrachloroethylene (2.3), p-xylene (2.3), benzene (2.3), m-xylene (2.4), toluene (2.4), triethylamine (2.4), 1,1,2-trichloro-1,2,2-trifluoroethane (2.4), o-xylene (2.6), diisopropyl ether (3.9), anisole (4.3), and diethyl ether (4.3). The value of the relative dielectric constant at 20°C shall be that measured in a relative dielectric constant test conducted in accordance with JIS C 2101:1999, Section 23, at a measurement temperature of 20°C.
[0043] Here, it was found that when an electrode active material layer is to be formed using an organic solvent having a relative dielectric constant of more than 4.5 at 20°C, the organic solvent reacts with the sulfide solid electrolyte, making it impossible to prepare the electrode active material layer. This is believed to be because an organic solvent having a too large relative dielectric constant has high polarity, and therefore is likely to react with the sulfide solid electrolyte. In contrast, by using an organic solvent having a relative dielectric constant of 4.5 or less at 20°C, the surface of the sulfide solid electrolyte is softened without substantially reacting with the sulfide solid electrolyte. As a result, it is believed that the contact at the interface between the electrode active material and the sulfide solid electrolyte is improved, thereby improving the ion conductivity at the interface, and reducing the internal resistance of the all-solid-state battery. However, this mechanism is based on speculation, and its correctness does not affect the technical scope of the present invention. In addition, from the viewpoint of promoting the expression of the effect based on the above mechanism, it is preferable that the organic solvent is in a liquid state at 20°C. In addition, based on the above mechanism, the effect of the configuration according to the present embodiment (reduction of the internal resistance of the all-solid-state battery) can be achieved even if the electrode active material is a positive electrode active material layer containing a positive electrode active material or a negative electrode active material layer containing a negative electrode active material. However, since an increase in the interface resistance due to contact with the sulfide solid electrolyte occurs significantly with the positive electrode active material, it is preferable that the electrode active material layer according to the present embodiment is a positive electrode active material layer containing a positive electrode active material.
[0044] From the viewpoint of excellent effect of reducing the internal resistance of the all-solid-state battery, the relative dielectric constant of the organic solvent contained in the electrode active material layer according to this embodiment is preferably 4.3 or less, more preferably 2.4 or less. The lower limit of the relative dielectric constant is not particularly limited, but is usually 1.5 or more. In addition, it is preferable that the electrode active material layer for an all-solid-state secondary battery according to this embodiment does not substantially contain an organic solvent having a relative dielectric constant greater than 4.5. The content of the organic solvent having a relative dielectric constant greater than 4.5 in the electrode active material layer is preferably 0.1 mass% or less, more preferably 0.05 mass% or less, even more preferably 0.01 mass% or less, and most preferably 0 mass% (below detection limit).
[0045] The content of the predetermined organic solvent in the electrode active material layer for an all-solid-state secondary battery according to this embodiment is 1.0 to 9.0 mass% relative to 100 mass% of the sulfide solid electrolyte contained in the electrode active material layer. According to the study by the present inventors, it was found that if the content is less than 1.0 mass% or exceeds 9.0 mass%, the effect of reducing the internal resistance of the all-solid-state battery by adding the predetermined organic solvent is not sufficiently exhibited. On the other hand, if the content is within the range of 1.0 to 9.0 mass%, the effect of reducing the internal resistance of the all-solid-state battery described above can be sufficiently exhibited. From the viewpoint of excellent effect of reducing the internal resistance of the all-solid-state battery, the content is preferably 1.0 to 5.0 mass% relative to 100 mass% of the sulfide solid electrolyte, and may be, for example, 1.1 to 5.0 mass%.
[0046] (Method of manufacturing electrode active material layer) The electrode active material layer for an all-solid-state secondary battery according to one embodiment of the present invention described above can be produced, for example, by forming an electrode mixture (a mixture of constituent materials of the electrode active material layer) in the state of a dry powder composition substantially not containing a liquid component such as a solvent into a sheet using sheet forming means such as a roll press.
[0047] Here, in this specification, the term "roll press machine" refers to a machine that includes at least a pair of cylindrical pressure rolls arranged in parallel with their outer circumferential surfaces facing each other and a rotation drive mechanism for the rolls, and that sandwiches the above-mentioned powder composition (electrode mixture) between the pair of rolls and rolls it into a sheet shape. The material and size of the rolls, the type of the rotation mechanism, and the arrangement of the rolls and the rotation mechanism are not particularly limited. In addition, the direction in which the electrode active material layer is discharged from between the pair of rolls is not particularly limited, and may be horizontal or downward.
[0048] The powder composition (electrode mixture) used as a raw material essentially contains a positive electrode active material, which is an essential component of the electrode active material layer, a sulfide solid electrolyte, and the above-mentioned predetermined organic solvent. In addition, the powder composition (electrode mixture) may contain a binder (preferably a fibrous binder in the positive electrode active material layer) and a conductive assistant as necessary.
[0049] The term "powder composition" refers to a substantially powdery mixture containing the constituent materials of the electrode active material. There is no particular limitation on the method for obtaining the powder composition, and each component constituting the powder composition may be added and mixed in any order. There is no particular limitation on the mixing means, and a method using a conventionally known mixing means such as a mortar, mixer, or mill may be appropriately adopted. Here, when the binder is a fibrous binder, there is no particular limitation on the method for blending the fibrous binder into the powder mixture, and the fibrous binder may be prepared separately and mixed with other components. In addition, when a fibrillizable binder, which is a precursor of the fibrous binder, is mixed with other components, a shear force may be applied to the fibrillizable binder to fibrillate it, thereby generating the fibrous binder in the powder composition.
[0050] In addition, when manufacturing the electrode active material layer according to this embodiment, it is preferable to mix the electrode active material with the above-mentioned predetermined organic solvent in advance to make the surface of the electrode active material particles coated with the organic solvent. Then, the electrode active material thus coated with the organic solvent may be used to prepare a powder composition (electrode mixture) by the above-mentioned method. In addition, when the electrode active material is a positive electrode active material whose particle surface is coated with an inorganic compound, it is preferable to coat the particle surface of the positive electrode active material with the inorganic compound and then mix it with an organic solvent.
[0051] Next, the powder composition for forming the electrode active material layer (positive electrode mixture) prepared above is formed into a sheet using a sheet forming means (hand roller or roll press machine) to obtain an electrode active material layer precursor. In this case, the specific sheet forming means may be selected in consideration of the thickness of each layer, etc.
[0052] In the above manufacturing method, the treatment using the roll press machine is preferably repeated while gradually decreasing the size of the gap until the non-treated object has a desired thickness. By performing such treatment, when a fibrous binder is used as the binder, it is also advantageous that a shear force can be applied to the binder during each roll press treatment to fibrillate it. The linear pressure applied to the treated object by the roll press machine is preferably 35 to 3500 N / cm. Here, the linear pressure applied to the treated object by the roll press machine means a linear pressure calculated from the load obtained by a load cell attached to the roll press machine and the width of the treated object after pressing. The rotation speed of the rolls of the roll press machine is not particularly limited, but is preferably 1 to 20 m / min from the viewpoint of maintaining a sufficient press retention time.
[0053] [Solid electrolyte layer] The solid electrolyte layer is interposed between the negative electrode and the positive electrode, and contains a solid electrolyte (usually as a main component). The solid electrolyte contained in the solid electrolyte layer is not particularly limited, and any solid electrolyte known in the art can be appropriately adopted, for example, the above-mentioned sulfide solid electrolyte, oxide solid electrolyte, and resin solid electrolyte. Among them, for the same reason as described above, it is preferable that the solid electrolyte layer also contains a sulfide solid electrolyte.
[0054] The content of the solid electrolyte in the solid electrolyte layer is preferably 50 to 100 mass %, and more preferably 90 to 100 mass %.
[0055] The solid electrolyte layer may further contain a binder in addition to the solid electrolyte. The binder is not particularly limited, and the binder described in the section on the electrode active material layer is used in the same manner. Examples of the binder contained in the solid electrolyte layer include polyvinylidene fluoride (PVDF), a compound in which hydrogen atoms of PVDF are substituted with other halogen elements, polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC). Among them, the binder contained in the solid electrolyte layer preferably contains polyvinylidene fluoride (PVDF) or styrene-butadiene rubber (SBR). The content of the binder in the solid electrolyte layer is not particularly limited, but is, for example, 1 to 10 mass%.
[0056] The thickness of the solid electrolyte layer varies depending on the intended configuration of the all-solid-state battery, but is usually 0.1 to 1000 μm, and preferably 10 to 100 μm.
[0057] [Negative electrode intermediate layer] The all-solid-state secondary battery preferably includes a negative electrode intermediate layer adjacent to the surface of the solid electrolyte layer facing the negative electrode current collector. The negative electrode intermediate layer contains, for example, at least one selected from the group consisting of a metal material capable of alloying with lithium and / or a carbon material capable of absorbing lithium ions, and a binder. The negative electrode intermediate layer is preferably conductive as a whole. The volume resistivity of the negative electrode intermediate layer is not particularly limited, but is preferably 10 2 The volume resistivity of the negative electrode intermediate layer is preferably 10 Ω·cm or less, and more preferably 10 Ω·cm or less. In this specification, the volume resistivity of the negative electrode intermediate layer is a value measured using an electrode resistance measurement system (manufactured by Hioki E.E. Corporation, product name: RM2610).
[0058] The negative electrode intermediate layer preferably contains at least one selected from the group consisting of metal materials that can be alloyed with lithium. By containing a metal material that can be alloyed with lithium in the negative electrode intermediate layer, lithium metal can be more uniformly deposited on the surface of the current collector. Specific examples of metal materials that can be alloyed with lithium include indium (In), aluminum (Al), silicon (Si), tin (Sn), magnesium (Mg), gold (Au), silver (Ag), zinc (Zn), and alloys containing at least one of these. Among them, the metal material preferably contains at least one selected from the group consisting of In, Al, Si, Sn, Mg, Au, Ag, and Zn, more preferably contains at least one selected from the group consisting of Ag, Mg, Zn, and Al, further preferably contains at least one selected from the group consisting of Ag, Mg, and Zn, and particularly preferably contains Ag.
[0059] The negative electrode intermediate layer preferably contains at least one selected from the group consisting of carbon materials capable of absorbing lithium ions, instead of or in addition to containing at least one selected from the group consisting of metal materials capable of alloying with lithium. When the negative electrode intermediate layer contains a carbon material capable of absorbing lithium ions, the precipitation and growth of lithium dendrites can be suppressed. Specific examples of carbon materials capable of absorbing lithium ions include carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), carbon nanotubes (CNT), graphite, hard carbon, etc. Among them, the carbon material preferably contains at least one selected from the group consisting of carbon black, and more preferably contains at least one selected from the group consisting of acetylene black, Ketjen Black (registered trademark), furnace black, channel black, and thermal lamp black.
[0060] According to a preferred embodiment, the negative electrode intermediate layer includes at least one kind of metal particles including the above-mentioned metal material capable of alloying with lithium, and at least one kind of carbon particles including the above-mentioned carbon material capable of absorbing lithium ions. By using both the metal particles and the carbon particles to form the negative electrode intermediate layer, an all-solid-state battery having even more excellent cycle characteristics can be obtained.
[0061] When both carbon particles and metal particles are used, the mass ratio of the carbon particles to the metal particles (carbon particles:metal particles) is preferably 10:1 to 1:1, more preferably 5:1 to 2:1, and even more preferably 4:1 to 2.5:1. The volume ratio of the carbon particles to the metal particles (carbon particles:metal particles) is preferably 99:1 to 70:30, and more preferably 95:5 to 75:25. When the compounding ratio (mass ratio or volume ratio) of the carbon particles to the metal particles is within the above range, an all-solid-state battery with even more excellent cycle characteristics can be obtained.
[0062] The negative electrode intermediate layer may further include a binder. The type of binder is not particularly limited, and any binder known in the art may be appropriately used. As the binder, the materials described in the section on the solid electrolyte layer may be used in the same manner.
[0063] The thickness of the negative electrode intermediate layer is not particularly limited, but is preferably 1 μm to 10 μm, more preferably 1.5 μm to 7 μm, and even more preferably 2 μm to 6 μm. When the thickness of the negative electrode intermediate layer is within the above range, it is possible to simultaneously suppress the precipitation and growth of lithium dendrites and the decrease in energy density.
[0064] Although one embodiment of the all-solid-state battery of the present invention has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0065] For example, the type of battery to which the all-solid-state lithium secondary battery according to the present invention is applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically coupled to one surface of a current collector and a negative electrode active material layer electrically coupled to the opposite surface of the current collector.
[0066] The following embodiments are also included within the scope of the present invention: an electrode active material layer according to claim 1 having the features of claim 2; an electrode active material layer according to claim 2 having the features of claim 3; an electrode active material layer according to claim 3 having the features of claim 4; an electrode active material layer according to any one of claims 2 to 4 having the features of claim 5; an electrode active material layer according to any one of claims 1 to 5 having the features of claim 6; an electrode active material layer according to any one of claims 1 to 6 having the features of claim 7; an electrode active material layer according to any one of claims 1 to 7 having the features of claim 8; an electrode active material layer according to any one of claims 1 to 8 having the features of claim 9; an electrode active material layer according to claim 9 having the features of claim 10; and an all-solid-state secondary battery using an electrode active material layer according to any one of claims 1 to 10. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples. However, the technical scope of the present invention is not limited to the following examples. In the following, the operations were performed in a glove box with a dew point of -68°C or less. Furthermore, the instruments and devices used in the glove box were thoroughly dried in advance.
[0068] <Example of evaluation cell preparation> [Comparative Example 1] (Preparation of solid electrolyte for positive electrode active material layer) A sulfide solid electrolyte (Li6PS5Cl, manufactured by Ampcera) was placed in a sealed container, connected to a heating vacuum drying device, and dried at 150°C for 6 hours to prepare a solid electrolyte for a positive electrode active material layer. The amount of organic solvent contained in the obtained solid electrolyte for a positive electrode active material layer was measured and found to be 0 mass%. Here, the amount of organic solvent contained in the solid electrolyte was calculated by placing 5 to 10 mg of a solid electrolyte sample in a thermogravimetric differential analysis (TG-DTA) device (TG-DTA8122, manufactured by Rigaku Corporation) and calculating the weight loss up to 140°C (same below).
[0069] (Preparation of Positive Electrode Active Material Layer) LiNi as the positive electrode active material 0.8 Mn 0.1 Co 0.1 A positive electrode mixture was prepared by mixing O2 (NMC811), the solid electrolyte for the positive electrode active material layer prepared above, a binder (PTFE) that had been fibrillated in advance, and a conductive assistant (carbon nanotubes) in a mass ratio of 80:13:2:5. Next, the positive electrode mixture was stretched into a sheet using a roll press machine, and punched out to a size of 10 mm in diameter to prepare a positive electrode active material layer.
[0070] (Preparation of evaluation cells) A stainless steel cylindrical convex punch (10 mm diameter, also serving as a negative electrode current collector) was inserted into one side of a cylindrical tube jig made by Macor (tube inner diameter 10 mm, outer diameter 23 mm, height 20 mm), and 80 mg of Li6PS5Cl (made by Ampcera), a sulfide solid electrolyte, was placed into the cylindrical tube jig from the top. Then, another stainless steel cylindrical convex punch was inserted to sandwich the sulfide solid electrolyte, and a solid electrolyte layer with a diameter of 10 mm and a thickness of approximately 0.6 mm was formed in the cylindrical tube jig by pressing it for 3 minutes at a pressure of 75 MPa using a hydraulic press. Next, the cylindrical convex punch inserted from the top was removed once, 25.5 mg of the positive electrode mixture prepared above was placed on one side of the solid electrolyte layer in the cylindrical tube, and a cylindrical convex punch (also serving as a positive electrode current collector) was inserted from the top again and pressed at a pressure of 300 MPa for 3 minutes to form a positive electrode active material layer with a diameter of 10 mm and a thickness of about 0.06 mm on one side of the solid electrolyte layer. Furthermore, the lower cylindrical convex punch (also serving as a negative electrode current collector) was removed, and a lithium foil (manufactured by Nilaco Corporation, thickness 0.20 mm) punched to a diameter of 8 mm and an indium foil (manufactured by Nilaco Corporation, thickness 0.30 mm) punched to a diameter of 9 mm were stacked as negative electrodes, and the indium foil was inserted from the bottom of the cylindrical tube jig so that it was located on the side of the solid electrolyte layer, and the cylindrical convex punch was inserted again and pressed at a pressure of 75 MPa for 3 minutes to form a lithium-indium negative electrode. In this manner, an all-solid-state secondary battery was produced in which the negative electrode current collector (punch), lithium-indium negative electrode, solid electrolyte layer, positive electrode active material layer, and positive electrode current collector (punch) were laminated in this order.
[0071] [Comparative Example 2] A sulfide solid electrolyte (Li6PS5Cl, manufactured by Ampcera) was placed in a sealed container, connected to a heating vacuum drying apparatus, and dried at 150°C for 6 hours. Then, toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., relative dielectric constant at 20°C: 2.4) was added to the solid electrolyte dried in this way to prepare a solid electrolyte for a positive electrode active material layer. The amount of toluene added was adjusted so that the content of toluene in the obtained solid electrolyte for a positive electrode active material layer was 0.1% by mass relative to 100% by mass of the sulfide solid electrolyte. The all-solid-state secondary battery of this comparative example was produced by the same method as in Comparative Example 1 described above, except that the solid electrolyte for a positive electrode active material layer prepared in this way was used.
[0072] [Example 1] The all-solid-state secondary battery of this example was produced in the same manner as in Comparative Example 2 described above, except that the amount of toluene added was adjusted so that the toluene content in the obtained solid electrolyte for the positive electrode active material layer was 1.0 mass % relative to 100 mass % of the sulfide solid electrolyte.
[0073] [Example 2] The all-solid-state secondary battery of this example was produced in the same manner as in Comparative Example 2 described above, except that the amount of toluene added was adjusted so that the toluene content in the obtained solid electrolyte for the positive electrode active material layer was 5.0 mass % relative to 100 mass % of the sulfide solid electrolyte.
[0074] [Comparative Example 3] An all-solid-state secondary battery of this comparative example was produced in the same manner as in Comparative Example 2 described above, except that the amount of toluene added was adjusted so that the toluene content in the obtained solid electrolyte for the positive electrode active material layer was 10.0 mass % relative to 100 mass % of the sulfide solid electrolyte.
[0075] [Example 3] The all-solid-state secondary battery of this example was produced in the same manner as in Example 1 described above, except that anisole (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., relative dielectric constant at 20° C.: 4.3) was used instead of toluene as the organic solvent.
[0076] [Comparative Example 4] An attempt was made to prepare a solid electrolyte for a positive electrode active material layer by the same method as in Comparative Example 2, using butyl acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., relative dielectric constant at 20°C: 4.8) instead of toluene as the organic solvent. However, when the sulfide solid electrolyte (Li6PS5Cl) was brought into contact with butyl acetate, the sulfide solid electrolyte reacted and discolored. For this reason, it was determined that butyl acetate was not an appropriate organic solvent, and no further experiments were performed.
[0077] <Example of evaluation of evaluation cell> The direct current resistance (DCR) of the evaluation cells prepared in the above examples and comparative examples was measured by the following method. A charge-discharge tester (HJ-SD8, manufactured by Hokuto Denko Corporation) was used for the measurement. First, the battery was placed in a thermostatic chamber, and after the cell temperature became constant, a current of 0.6 mA / cm was applied. 2 Constant current constant voltage charge up to 4.3V at a current density of 0.01mA / cm 2 The charge / discharge capacity was set at 0.2 mA / cm2, and then constant current discharge was performed at the same current density to 2.5 V. The capacity value per mass of the positive electrode active material (mAh / g) was calculated from the charge / discharge capacity value at this time and the mass of the positive electrode active material contained in the positive electrode. Next, the capacity value was calculated as 100% and then discharged at 0.2 mA / cm2 until the capacity reached 50% (SOC50%). 2 After a 30-minute pause, the discharge was continued at a constant current density of 6 mA / cm 2 The direct current resistance (DCR) was calculated from the voltage drop and current value according to Ohm's law. The results are shown in Table 1 below.
[0078] [Table 1]
[0079] From the results shown in Table 1, it can be seen that when the electrode active material layer of the all-solid-state secondary battery contains, in addition to the electrode active material and the sulfide solid electrolyte, a predetermined amount of an organic solvent having a relative dielectric constant of 4.5 or less at 20°C relative to 100% by mass of the sulfide solid electrolyte, the internal resistance (DCR resistance) of the all-solid-state secondary battery can be reduced. It can also be seen that an organic solvent with a smaller relative dielectric constant (for example, toluene, etc.) is preferable. Furthermore, it can also be seen that the effect of reducing the internal resistance is improved when the content of the organic solvent in the electrode active material layer is within a range of 1.0 to 5.0% by mass relative to 100% by mass of the sulfide solid electrolyte. [Explanation of symbols]
[0080] 10a laminated secondary battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 14 negative electrode intermediate layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.
Claims
1. An electrode active material; A sulfide solid electrolyte; an organic solvent having a relative dielectric constant of 4.5 or less at 20°C; Including, The content of the organic solvent is 1.0 to 9.0% by mass relative to 100% by mass of the sulfide solid electrolyte.
2. The electrode active material layer for an all-solid-state secondary battery according to claim 1 , which is a positive electrode active material layer containing a positive electrode active material as the electrode active material.
3. The electrode active material layer for an all-solid-state secondary battery according to claim 2 , wherein the surfaces of the particles of the positive electrode active material are coated with an inorganic compound other than the positive electrode active material.
4. 4. The electrode active material layer for an all-solid-state secondary battery according to claim 3, wherein the inorganic compound contains lithium, oxygen, and one or more selected from the group consisting of niobium, phosphorus, boron, silicon, germanium, titanium, and zirconium.
5. The electrode active material layer for an all-solid-state secondary battery according to claim 2 , wherein the positive electrode active material layer contains a fluorine-containing polymer compound as a binder.
6. The electrode active material layer for an all-solid-state secondary battery according to claim 1, wherein the content of the organic solvent is 1.0 to 5.0% by mass relative to 100% by mass of the sulfide solid electrolyte.
7. 2. The electrode active material layer for an all-solid-state secondary battery according to claim 1, wherein the sulfide solid electrolyte contains an S element, a Li element, and a P element.
8. The electrode active material layer for an all-solid-state secondary battery according to claim 1 , wherein the organic solvent is in a liquid state at 20° C.
9. The electrode active material layer for an all-solid-state secondary battery according to claim 1 , wherein the relative dielectric constant is 4.3 or less.
10. The electrode active material layer for an all-solid-state secondary battery according to claim 9 , wherein the organic solvent has a relative dielectric constant of 2.4 or less.
11. An all-solid-state secondary battery comprising the electrode active material layer for an all-solid-state secondary battery according to any one of claims 1 to 10.
Citation Information
Patent Citations
Solid electrolyte
WO2020203224A1